Opportunities and Challenges in the Implementation of Collaborative Strategic Reading (CSR) in Teaching Reading Comprehension - Agna, Aura Roro Rif'aning; Rofiq, Annur; Ariani, Musli (EFL Education Journal, 2024)
This study aims to discover how CSR (Collaborative Strategic Reading) creates opportunities and challenges for teachers and students in reading comprehension. This study was framed by a case study design. The data were collected using classroom observation and semi-structured interviews with participant consent. The participant of this study was a teacher at Senior High School in Jember. The observation and thematic analysis results revealed that CSR can create opportunities and challenges for teachers and students. The opportunities for CSR for students are boosting comprehension, encouraging student engagement, and increasing knowledge retention. On the other hand, the challenges faced by the teacher are time management, discussion management, and counting on individual learning.